2006
DOI: 10.1002/uog.2769
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional ultrasound findings of spondylocostal dysostosis in the second trimester of pregnancy

Abstract: Spondylocostal dysostosis (SCD) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…It has been suggested to evaluate the position of the conus medullaris by identifying the lowest fetal rib (T12) [23] or to measure the distance between the co-nus medullaris and the top of the first sacral vertebra. In our case of spondylocostal dysplasia, even though it is frequently reported, no spinal cord malformation was observed [24] .…”
Section: Discussioncontrasting
confidence: 53%
“…It has been suggested to evaluate the position of the conus medullaris by identifying the lowest fetal rib (T12) [23] or to measure the distance between the co-nus medullaris and the top of the first sacral vertebra. In our case of spondylocostal dysplasia, even though it is frequently reported, no spinal cord malformation was observed [24] .…”
Section: Discussioncontrasting
confidence: 53%
“…Molecular prenatal diagnosis of SCD has been described [Whittock et al, 2003]. Increased nuchal translucency in the first trimester has been reported when the fetus is affected by SCD [Eliyahu et al, 1997; Hull et al, 2001; Kauffmann et al, 2003; Wong et al, 2006]. Nuchal oedema has been described in at least 20 different skeletal dysplasias, with the underlying mechanism postulated to be intrathoracic compression leading to venous congestion in the head and neck [Souka et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Case reports of abnormal ribs shown on 3-dimensional ultrasonography (3DUS) in association with spondylothoracic or spondylocostal dysostosis have also been reported. 3,5,6 To our knowledge, no data regarding the ultrasonographic demonstration of the number of fetal ribs have been reported. A recent case report emphasized the association of an abnormal number of fetal ribs and trisomy 21; however, the exact importance of an abnormal number of ribs is not known.…”
mentioning
confidence: 99%
“…None of our fetuses had severe spondylocostal dysostosis, which is a rare congenital disorder characterized by short-trunk dwarfism associated with rib and vertebral anomalies. 5 Benoit 4 described the use of 3D imaging in evaluation of the fetal skeleton. He suggested that 3DUS is the investigation tool of choice for studying the fetal skeleton at any time during gestation.…”
mentioning
confidence: 99%
See 1 more Smart Citation